2006
DOI: 10.1007/s00127-006-0042-6
|View full text |Cite
|
Sign up to set email alerts
|

The quality of life of people with schizophrenia living in community in Rio de Janeiro, Brazil

Abstract: A total of 136 patients participated in the study. Most of them were single and lived with their relatives, had low educational level, were unemployed and had low income. A great number of the interviewed did not have any social contact outside the family and leisure activity, except watching television and/or listening to the radio. Finances and work situation had the lowest satisfaction level. Educational level, presence of positive and depressive symptoms, hospital admissions were negatively associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
6
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 39 publications
7
6
1
2
Order By: Relevance
“…Regarding the association of socio‐demographic characteristics and QOL, we found that people who were employed and had a higher monthly household income perceived greater satisfaction with their lives, suggesting that employment plays an important role in the daily life of an individual. These findings were consistent with those of a study undertaken in Hong Kong (Chan & Yu 2004) and Brazil (de Souza & Coutinho 2006). As Chan and Yu (2004) noted, work not only provides financial remuneration but also enhances individuals’ integration into society and promotes the perceptions of their worth.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the association of socio‐demographic characteristics and QOL, we found that people who were employed and had a higher monthly household income perceived greater satisfaction with their lives, suggesting that employment plays an important role in the daily life of an individual. These findings were consistent with those of a study undertaken in Hong Kong (Chan & Yu 2004) and Brazil (de Souza & Coutinho 2006). As Chan and Yu (2004) noted, work not only provides financial remuneration but also enhances individuals’ integration into society and promotes the perceptions of their worth.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with other first-episode samples. [31][32][33][34] Mean household income (R2 560 ($365) per month) was less than half that of the general population (R5 360 ($777) per month), consistent with previous findings.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, the mean difference in a few domains turned out to be very small, even if it reached a statistically significant level when analyzed by Cohen's standard, and little evidence of systematic bias in the patient-proxy rating was found. In accordance with our results, past studies on patient-proxy difference in QoL measurement have found that the mean differences between two ratings are small and of questionable clinical meaning, suggesting that the benefit of using proxy responses [28,33].…”
Section: Patient-proxy Agreement At Group Levelsupporting
confidence: 94%
“…(standardized mean differences 0.0-0.3 in schizophrenia group, 0.0-0.5 in bipolar disorder group) This finding is consistent with previous studies reporting the median standardized differences of about 0.1 to 0.3 [28,31,33]. The degree of difference between mean scores that can be allowed before one can conclude that agreement is satisfactory is controversial.…”
Section: Patient-proxy Agreement At Group Levelsupporting
confidence: 92%
See 1 more Smart Citation